DEVELOPMENT AND INTEGRATION OF SEARCH ROBOT (SR PYROTERRA) WITH THERMAL SENSOR - Arenajo, James Emanuel G.; Castillon, Kezia Mae B. (President University, 2024)
Rescue robots are essential instruments during emergencies and natural disasters since they are outfitted with sophisticated thermal sensors, can withstand extreme temperatures, and can move in close proximity to the person in need. By operating in environments that are hazardous and unsafe for human responders such as burning or collapsed buildings, toxic chemical spills, or extreme weather conditions, rescue robots minimize risk and improve response durations. Generally, this study aimed to determine the functionality in terms of a) duration of flight, capabilities of device thermal range detection, c) device’s control range. The electrical parts of the robot prototype were tested to determine if they are functional before the robot was assembled. In constructing the Search Robot, we used Phantom 3 Motherboard and Motors, Thermal Sensor, 3D modelled parts using Fusion 360 were then sliced using CURA and 3D printed using the Ender 3D printer. The robot was programmed with embedded C++ coding and were all assembled and placed with 3D printed parts and attachments. The functionality of the robot in terms of detecting the person and fire was tested two times. It can be determined in the thermal sensor if there is a person or object by displaying a dark blue highlight, and fires can be detected by the sensor and the highlight’s color may vary depending on the flame’s temperature, mostly being yellow to red highlights. The success rate was computed to determine the average functionality. A 100% success rate shows that SR Pyroterra Thermatron can successfully navigate and locate the person.